Analisis Risiko Dan Strategi Mitigasi Risiko Pada Layanan Fintech Syariah Peer To Peer Lending Di Masa Pandemi Covid-19 (Studi Kasus : PT. Alami Fintek Sharia) - Diawati Diawati; Nur Diana; M Cholid Mawardi (Fakultas Ekonomi dan Bisnis Universitas Islam Malang, 2022)
This study was used to determine risk analysis and risk mitigation strategies in the peer to peerlending sharia fintech service PT Alami Fintek Syariah. This research includes qualitative methods, usingprimary and secondary data sources. Data collection techniques are observation, interviews, anddocumentation. The risks in ALAMI P2P lending sharia fintech services are: 1) Character Risk of SMEFinancing Candidates, 2) Risk of Decrease in Paying Ability of SMEs, 3) Side Streaming Risk, 4) PayerCapacity Risk, 5) Legal Risk, and 6) Cybersecurity. From the risk analysis, the results of risk mitigationin ALAMI P2P lending services are: 1) Paying attention to the Competence of the Risk ManagementTeam, 2) Assessing Payer Capacity, 3) Establishing SME Project Ratings, 4) Cooperating with PrivateCredit Bureaus, 5) Using Second Way Out, 6) Use of Virtual Accounts, 7) Implement Due Diligence andPrudence, 8) ISO27001 Cybersecurity and 9) Periodic Industry Updates.